AETA 2017 - Recent Advances in Electrical Engineering and Related Sciences: Theory and Application - Duy, Vo Hoang; Dao, Tran Trong; Zelinka, Ivan; Kim, Sang Bong; Phuong, Tran Thanh (Lecture Notes in Electrical Engineering,, 2018)
This proceedings book gathers papers presented at the 4th International Conference on Advanced Engineering Theory and Applications 2017 (AETA 2017), held on 7-9 December 2017 at Ton Duc Thang University, Ho Chi Minh City, Vietnam. It presents selected papers on 13 topical areas, including robotics, control systems, telecommunications, computer science and more. All selected papers represent interesting ideas and collectively provide a state-of-the-art overview. Readers will find intriguing papers on the design and implementation of control algorithms for aerial and underwater robots, for mechanical systems, efficient protocols for vehicular ad hoc networks, motor control, image and signal processing, energy saving, optimization methods in various fields of electrical engineering, and others. The book also offers a valuable resource for practitioners who want to apply the content discussed to solve real-life problems in their challenging applications. It also addresses common and related subjects in modern electric, electronic and related technologies. As such, it will benefit all scientists and engineers working in the above-mentioned fields of application.